Implementation Challenges of the Regional Government Information System (SIPD): Comparative Evidence from Three Indonesian Local Governments - Tumanggor, Rinawati; Berutu, Minar; Adipati, Atikah Aripah; Piantel; Irawan (CV Raskha Media Group, 2025)
The implementation of the Regional Government Information System (SIPD) represents a strategic initiative by the Indonesian government to achieve effective, transparent, and accountable governance. However, SIPD implementation faces various challenges that hinder the achievement of these objectives. Objective: This study aims to analyze the challenges of SIPD implementation in three Indonesian local governments and identify factors influencing its successful implementation. Method: This research employs a comparative descriptive qualitative approach with case studies in Nganjuk Regency, Nias Regency, and Medan City. Data were collected through in-depth interviews with 29 informants, direct observation, and document review. Data analysis used the Miles and Huberman interactive model with Van Meter and Van Horn's policy implementation theory framework. Results: The study identified three main categories of challenges: (1) Technical challenges including system instability, incomplete features, and integration issues; (2) Human resource challenges encompassing capacity deficiencies, change resistance, and training limitations; (3) Policy coordination challenges involving weak central-local communication and unclear standardization. All three regions showed similar challenge patterns despite varying intensities. Conclusion: SIPD implementation requires a holistic approach integrating technical system improvements, human resource capacity building, and strengthened policy coordination. Implementation success depends on leadership commitment, infrastructure readiness, and sustained support from the central government.